Voices from the South Digital Arts and Humanities - du Preez, Amanda (AOSIS, 2018)
This volume captures the status of digital humanities within the Arts in South Africa. The primary research methodology falls within the broader tradition of phenomenological hermeneutics, with a specific emphasis on visual hermeneutics. Some of the tools utilised as part of the visual hermeneutic methods are geographic information system (GIS) mapping, sensory ethnography and narrative pathways. Digital humanities is positioned here as the necessary engagement of the humanities with the pervasive digital culture of the 21st century. It is posited that the humanities and arts, in particular, have an essential role to play in unlocking meaning from scientific, technological and data-driven research. The critical engagement with digital humanities is foregrounded throughout the volume, as this crucial engagement works through images. Images (as understood within image studies) are not merely another form of text but always more than text. As such, this book is the first of its kind in the South African scholarly landscape, and notably also a first on the African continent. Its targeted audience include both scholars within the humanities, particularly in the arts and social sciences. Researchers pursuing the new field of digital humanities may also find the ideas presented in this book significant. Several of the chapters analyse the question of dealing with digital humanities through representations of the self as viewed from the Global South. However, it should be noted that self-representation is not the only area covered in this volume. The latter chapters of the book discuss innovative ways of implementing digital humanities strategies and methodologies for teaching and researching in South Africa.